2012
DOI: 10.1016/j.jclinepi.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of clinical history affects accuracy of interpretive performance of screening mammography

Abstract: Objective To examine how use of clinical history affects radiologist's interpretation of screening mammography. Study Design and Setting Using a self-administered survey and actual interpretive performance, we examined associations between use of clinical history and sensitivity, false-positive rate, recall rate, positive predictive value, after adjusting for relevant covariates using conditional logistic regression. Results The majority of radiologists the 216 radiologists surveyed (63.4%) reported usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…For instance, collateral clinical information may not be available for out-of-network patients whose medical data do not reside in the institutional electronic health record. Studies have demonstrated that insufficient clinical data available to the interpreting radiologist (ie, either cryptic or incorrect information) at the point of care increases the likelihood of a diagnostic miss [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, collateral clinical information may not be available for out-of-network patients whose medical data do not reside in the institutional electronic health record. Studies have demonstrated that insufficient clinical data available to the interpreting radiologist (ie, either cryptic or incorrect information) at the point of care increases the likelihood of a diagnostic miss [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretive performance of screening mammography is known to vary by patient (4, 23–25), radiologist (4–7, 9, 11, 24–30) , and facility level characteristics. (30, 31) However, the extent to which screening mammography performance varies by the radiologic technologist has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…(4, 23, 24) Radiologist level factors found to affect performance include time since graduation from residency, breast-imaging fellowship/training, annual interpretative volume, years of mammographic imaging and interpretation, and primary affiliation with an academic medical center. (4–7, 9, 24–26, 28–30) Facility level characteristics that may affect performance include volume, screening versus diagnostic mammography mix, having breast imaging specialists interpreting the examinations, and having audits two or more times per year.…”
Section: Discussionmentioning
confidence: 99%
“…There are established variables affecting mammography recall rates (RRs) and cancer detection rates (CDRs). These include patient factors such as breast density [2], age [3,4], use of hormone replacement therapy [2,5], interval since prior mammographic study [3], family history [6], and prior biopsy results [6]. Interpreting physician factors may include radiologist's sex [7], experience [7,8], practice setting [9], annual case volume [10], and fellowship training [7,11].…”
Section: Introductionmentioning
confidence: 99%